Studies in humans and mice implicate neurocan in the etiology of mania - Miró, Xavier; Rietschel, Marcella (The American journal of psychiatry, 2012)
Objective: Genome-wide association has been reported between the NCAN gene and bipolar disorder. The aims of this study were to characterize the clinical symptomatology most strongly influenced by NCAN and to explore the behavioral phenotype of Ncan knockout (Ncan−/−) mice.MethodGenotype/phenotype correlations were investigated in patients with bipolar disorder (N=641) and the genetically related disorders major depression (N=597) and schizophrenia (N=480). Principal components and genotype association analyses were used to derive main clinical factors from 69 lifetime symptoms and to determine which of these factors were associated with the NCAN risk allele. These analyses were then repeated using the associated factor(s) only in order to identify the more specific clinical subdimensions that drive the association. Ncan−/− mice were tested using diverse paradigms, assessing a range of behavioral traits, including paradigms corresponding to bipolar symptoms in humans.Results In the combined patient sample, the NCAN risk allele was significantly associated with the “mania” factor, in particular the subdimension “overactivity.” Ncan−/− mice were hyperactive and showed more frequent risk-taking and repetitive behaviors, less depression-like conduct, impaired prepulse inhibition, amphetamine hypersensitivity, and increased saccharin preference. These aberrant behavioral responses normalized after the administration of lithium.ConclusionsNCAN preferentially affected mania symptoms in humans. Ncan−/− mice showed behavioral abnormalities that were strikingly similar to those of the human mania phenotype and may thus serve as a valid mouse model.